1991
DOI: 10.1210/jcem-72-3-635
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Efficacy and Safety of Pergolide and Bromocriptine in the Treatment of Hyperprolactinemia*

Abstract: in these 24-week studies comprising a total of 157 hyperprolactinemic patients, a once daily administration of pergolide was shown to be as safe and effective as the two to four times daily ingestion of bromocriptine. Longer-acting dopamine agonists like pergolide that can be taken once daily, are likely to increase the ease to adherence to the therapeutic regimen. This might result in a higher compliance to medical treatment of hyperprolactinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 20 publications
1
18
0
1
Order By: Relevance
“…The overall PRL lowering effect of roxindol was comparable to that observed during previous bromocriptine therapy. Similar results have been obtained with ergot derivatives in several studies [9,12] as well as with another non-ergot drug, quinagolide (CV 205-502), in a double-blind trial [19].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The overall PRL lowering effect of roxindol was comparable to that observed during previous bromocriptine therapy. Similar results have been obtained with ergot derivatives in several studies [9,12] as well as with another non-ergot drug, quinagolide (CV 205-502), in a double-blind trial [19].…”
Section: Discussionsupporting
confidence: 83%
“…The therapeutic efficiency is shared by other ergot derivatives with dopamine agonist activity such as lisuride [2], mesulergine [9], metergoline [6], pergolide [12], and terguride [7], as are the disadvantages. These include a high frequency of adverse reactions, sometimes even prohibiting effective treatment, and lack of response to therapy in a minority of patients.…”
mentioning
confidence: 99%
“…In short-term studies, pergolide has been shown to effectively lower PRL levels. In an open-label, randomized, controlled, multicenter study, Lamberts and Quik (213) reported that bromocriptine and pergolide were equally effective in lowering serum PRL levels and in inducing tumor shrinkage; a high incidence of adverse events, such as nausea, dizziness, vomiting, asthenia, headache, and decrease in blood pressure, was reported with both drugs. Data concerning the reduction of macroprolactinoma size by pergolide are limited (214 -217).…”
Section: Pergolidementioning
confidence: 99%
“…Although pergolide is a potent inhibitor of prolactin secretion [27], the drug has never found an important place in the treatment of hyperprolactinaemic states. In a double-blind study involving a total of 157 hyperprolactinaemic patients the efficacy and tolerability of bromocriptine and pergolide were found to be the same, while the incidence and type of side-effects to both dopamine agonists were similar [28].…”
Section: Pergolidementioning
confidence: 96%